Yeah! - Bagge, Peter 1957- (Homage Comics, 1999)
The all-girl band Yeah!...consisting of Krazy, Honey, and WooWoo...have achieved intergalactic stardom on every planet except Earth, where they struggle to achieve fame in suburban New Jersey
Keywords: Rock groups -- Comic books, strips, etc; Women rock musicians -- Comic books, strips, etc; Graphic novels; Comic